RANCANG BANGUN MEDIA PRAKTIK STAND FINAL DRIVE EXCAVATOR EX100-5 - Anwar Mazmur; Yosrihard Basongan (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Based on a survey in the heavy equipment virgin workshop, the problems experienced by students of the heavy equipment maintenance study program are limited practicum equipment and lack of student skills on maintenance and repair of heavy equipment final drives. The purpose of this research is to design and make a final drive stand frame and analyze the strength of the final drive stand frame so that it can be used as a practicum tool in the Heavy Equipment Maintenance Workshop of the Mechanical Engineering Department of the Ujung Pandang State Polytechnic. The working process includes: 1) determining the material, 2) calculating the selected material, 3) designing the frame, 4) doing the frame work, 5) trial & error trials, 6) using the tool. The results obtained are the maximum shear stress that occurs in the welding connection between the shaft and the support arm (holder) of the final drive is 3.98 N/mm2 and the maximum tensile stress that occurs in the bolt connection between the support arm (holder) and the final drive is 1. 99 N/mm2, making it safe to withstand a load weight of 2250 N, the maximum bending stress that occurs in the final drive stand frame is 78.125 N/mm2 which is less than the allowable tensile stress of the frame material, making it safe to withstand a load weight of 2250 N and the results of the final drive stand trial through the final drive overhaul process obtained an increase in the efficiency of the total overhaul time is 48.63%.